Impact of Antibiotic Resistance on Pharmacy Practices in Indonesian Hospitals - Sari, Wahyu Kartika; Elvina Triana Putri; Putri Juanti (Jurnal Ar Ro'is Mandalika (Armada), 2026)
Antibiotic resistance (ABR) is a growing public health threat worldwide, with significant implications for pharmacy practices, particularly in Indonesian hospitals. This study aims to explore the impact of ABR on pharmacy practices in Indonesia through a qualitative literature review, using a library research methodology. By examining peer-reviewed articles, government reports, and other relevant sources, the study identifies key challenges and barriers faced by pharmacy professionals in managing ABR. Findings indicate that ABR prevalence in Indonesia is high, driven by the overuse and misuse of antibiotics, and exacerbated by inconsistent pharmacist knowledge and training. While antimicrobial stewardship programs (ASPs) are implemented in many hospitals, their effectiveness remains limited due to resource constraints, inadequate staffing, and insufficient integration into clinical practices. Additionally, the study highlights the underutilization of pharmacists in clinical decision-making, despite their crucial role in optimizing antibiotic use. The lack of rapid diagnostic tools and the cultural expectation for antibiotics further complicate ABR management. This study emphasizes the need for enhanced pharmacist education, better resource allocation, and a more integrated approach to antimicrobial stewardship. Future research should focus on evaluating the effectiveness of ASPs in resource-limited settings, the impact of public education campaigns, and the integration of rapid diagnostic technologies to reduce ABR.